Development and validation of a genome-wide InDel marker set discriminating the alleles between the BB-genome Oryza species and rice (O. sativa) - Malabanan-Bauan, Katrina B.; Hechanova, Sherry Lou; Ahn, Eok-Keun; Li, Charng-Pei; Choi, Il-Ryong; Hernandez, Jose E.; Jena, Kshirod K.; Kim, Sung-Ryul (Elsevier, 2023)
Wild relatives of cultivated rice (Oryza sativa) belonging to the genus Oryza are regarded as ‘genetic reservoirs’ for rice improvement. Their genes are transferable to cultivated rice through crossing and they have been contributing significantly to rice variety improvement by introgression of their diverse valuable traits, especially biotic stress resistance. Moreover, active use of wild rice resources might be one of the ideal solutions to seek novel or superior alleles/genes to cope with climate change and stable high-yield rice production. DNA markers are essential tools for genetic analysis and breeding. However, to date, there are no suitable DNA marker sets for BB-genome species (O. punctata). In this study, we developed a genome genome-wide InDel marker set evenly distributed (∼2 Mb intervals) across the 12 chromosomes for BB-genome species. The markers were validated by PCR-agarose gel analysis with BB-genome containing species: four accessions each of O. punctata (BB) and O. minuta (BBCC). Out of the 191 InDel markers designed, 184 (96.3%) and 138 (72.2%) were able to differentiate the alleles between O. sativa and O. punctata and between O. sativa and O. minuta respectively. The same marker sets were also tested in other genome types species (CC, CCDD, EE, FF, GG, HHJJ, and KKLL) and one accession of Leersia perrieri (a sister genus to Oryza). The number of polymorphic markers (O. sativa vs other genome types) was drastically reduced in other genome types. In contrast, the number of markers showing no PCR amplification increased, especially in FF, GG, HHJJ, and KKLL species. This suggests that the development of genome type-specific marker sets would be more efficient rather than testing random InDel markers. The newly developed InDel markers maybe be useful for the identification of valuable genetic factors from the BB or BBCC-genome species and also for transferring the identified genes/QTLs into elite variety backgrounds.